2020
DOI: 10.1186/s40168-020-00895-w
|View full text |Cite
|
Sign up to set email alerts
|

Environmental shaping of the bacterial and fungal community in infant bed dust and correlations with the airway microbiota

Abstract: Background: From early life, children are exposed to a multitude of environmental exposures, which may be of crucial importance for healthy development. Here, the environmental microbiota may be of particular interest as it represents the interface between environmental factors and the child. As infants in modern societies spend a considerable amount of time indoors, we hypothesize that the indoor bed dust microbiota might be an important factor for the child and for the early colonization of the airway microb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 57 publications
2
22
0
2
Order By: Relevance
“…In this study, we applied the FunOMIC pipeline to a set of nearly 2,700 metagenomic human samples representing human microbiomes of different body sites from individuals with different health status and from different geographical regions. We corroborated previous human mycobiome results showing that the species S. cerevisiae , C. albicans , and M. restricta dominate the fungal communities in different human body sites [46] , [47] , [48] , [49] . We found that geography and health status were the two most important factors contributing to the variabilities of human mycobiome taxonomic and functional compositions.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we applied the FunOMIC pipeline to a set of nearly 2,700 metagenomic human samples representing human microbiomes of different body sites from individuals with different health status and from different geographical regions. We corroborated previous human mycobiome results showing that the species S. cerevisiae , C. albicans , and M. restricta dominate the fungal communities in different human body sites [46] , [47] , [48] , [49] . We found that geography and health status were the two most important factors contributing to the variabilities of human mycobiome taxonomic and functional compositions.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, lung microbiota might be affected by many external factors. Environmental factors such as bed dust could influence airway microbiota compositions among infants [ 23 ]. Maternal dietary intervention with long-chain fatty acids and vitamin D supplementation can affect the infant airways but not the infant fecal microbiota [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 16S rRNA gene amplicon analysis remains the standard approach for the cultivation independent investigation of microbiota, and the accuracy of these analyses depends mainly on primer selections [ 25 ]. The nine hypervariable regions (V1-V9) of 16S rRNA gene are frequently used for determining of the bacterial taxonomy in the diverse microbial populations [ 4 , 14 , 23 ]. In general, high-throughput short-read sequencing of the 16S rRNA gene amplicon based on the Illumina MiSeq platform specifically targets the V3-V4 hypervariable region [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We examined the microbiota using 16S rRNA gene amplicon sequencing, as previously described [ 26 , 27 ]. In brief, DNA was extracted from both sample types using the PowerMag® Soil DNA Isolation Kit (MO-BIO Laboratories), after which the hypervariable V4 region of the 16S rRNA gene was amplified, using the modified broad range primers 515F and 806R.…”
Section: Methodsmentioning
confidence: 99%